Порівняльний аналіз методів генерації синтезованих тестових даних у реляційних базах даних - Башкіров, М. О. (ХНУРЕ, 2024)
The work examines effective methods for generating synthetic test data for relational database systems. Three main approaches are reviewed: cyclic generation, recursive CTEs, and temporary tables. Key criteria for comparative analysis are identified: speed, resource use, scalability, complexity. By studying the strengths and weaknesses of each method, practical recommendations for selecting optimal test data generation strategies are developed. The work will benefit software testing specialists in choosing data generation methods to improve testing quality.
Keywords: синтезовані тестові дані; реляційні базах даних